2018
DOI: 10.1080/17515831.2018.1435343
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear characteristics of vegetable oils using nanoparticles for sustainable lubrication

Abstract: The non biodegradability associated with the mineral oils, ever increasing global demand for lubricants and limited crude oil resources have led to a paradigm shift of focus from nonrenewable to renewable. The problems of friction and wear being innate to engineering applications, further poses environmental hazards by way of more fuel consumption and wear debris. The present paper is aimed to highlight the research studies carried out to exploit the addition of nanoparticle additives in vegetable oils. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(53 citation statements)
references
References 106 publications
0
53
0
Order By: Relevance
“…The hazardous effects and rapid depletion of petroleum-based lubricants are driving the environmental legislation authorities to find its suitable replacement for industrial applications. 1 The petroleum-based lubricants are non-renewable with low biodegradability and high ecotoxicity. As a result, researchers have suggested the use of bio-oils as a suitable replacement for petroleum-based lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…The hazardous effects and rapid depletion of petroleum-based lubricants are driving the environmental legislation authorities to find its suitable replacement for industrial applications. 1 The petroleum-based lubricants are non-renewable with low biodegradability and high ecotoxicity. As a result, researchers have suggested the use of bio-oils as a suitable replacement for petroleum-based lubricants.…”
Section: Introductionmentioning
confidence: 99%
“…Double bonds are the active sites for oxidation resulting in the thermal degradation of the oil. Consequently, the oils with high monounsaturated fatty acids are considered as most desirable candidates for lubrication purpose [5]. Jayadas et al [6] further conducted a comparative tribological study of coconut oil and mineral oil on a four-ball tester and reported an improvement in the coefficient of friction with a negative effect on wear rate as compared to the petroleum-based lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…Friction and wear are events that occur unexpectedly in engineering projects and waste is a contaminant that becomes an environmental problem. Thus, the addition of nanoparticle additives in vegetable oils becomes an important alternative to minimize these risks [20].…”
Section: Resultsmentioning
confidence: 99%